ANALISIS PARTISIPASI DAN PERSEPSI MASYARAKAT PETANI TERHADAP RESTORASI DAN PRESERVASI HUTAN - Nurmalia, Ana; Handono, Wahyu (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
Polemics on forest damage and socio-economic problems that arise then what can be done to balance management as an element of economic support but still do not forget the importance is to actively participate in saving by restoration and preservation of forests. Researchers are interested in conducting a more in-depth study of